Cherry angioma: A case-control study - Ramah I Nazer; Rahaf H Bashihab; Wedad H Al-Madani; Aamir A Omair; Mohammed I AlJasser (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Cherry angiomas (CAs) are very common asymptomatic vascular skin lesions. There are only a few studies on CAs in the literature and those assessing risk factors of CAs are scarce. The aim of our study was to determine risk factors for the development of CAs. MATERIALS AND METHODS: A case-control study was conducted at a tertiary care center in Riyadh, Saudi Arabia. Patients underwent a full-body examination for CAs. Demographics and other data including medical history and medications were extracted from electronic medical records. RESULTS: A total of three hundred patients were enrolled: one hundred cases with at least five CAs and two hundred controls without CAs. Bivariate analysis identified benign prostatic hyperplasia (odds ratio [OR]: = 2.591), malignancy (OR = 2.567), tamsulosin (OR = 3.171), and clopidogrel (OR = 0.321) as statistically significant associations. After multivariate logistic regression analysis, only tamsulosin (OR = 3.475, P = 0.009) and clopidogrel (OR = 0.281, P = 0.028) were found to be independent risk factors for CAs. Malignancies tended to be more associated with CAs, but this did not reach statistical significance (P = 0.07). CONCLUSION: Tamsulosin is a possible risk factor for the development of CAs. Clopidogrel seems to have a protective role preventing the development of CAs.